ANALYSIS OF FOOD WASTE IN CLASS III PATIENTS ON THE ADEQUACY OF ENERGY AND MACRONUTRIENTS IN THE FOOD SERVICE IN RSUD KANJURUHAN MALANG DISTRICT - Mahala, Silvia Zahroini; Nurmayanti, Rani (Pusat Unggulan IPTEK Poltekkes Kemenkes Malang, 2025)
Background: Food service is a set of activities ranging from menu planning to food distribution to consumers to achieve optimal health status through proper nutrition. Including recording, reporting and evaluation activities (Aritonang et al., 2012). According to the Ministry of Health of the Republic of Indonesia (2013) Food organization is the provision of quality food according to nutritional needs, cost, safe and acceptable to consumers in order to achieve optimal nutritional status. Objective: To analyze the residue of ordinary food in class III patients against the adequacy of energy and macronutrients in the provision of food at Kanjuruhan Hospital Malang Regency. Methods: This type of research is descriptive observational. The research was conducted by observing the remaining food eaten by class III patients at the Nutrition Installation of Kanjuruhan Hospital, Malang Regency. Result : The menu on days 1 and 3 did not meet the hospital's minimum service standards, which were still above 20%, while the menu on day 2 met the hospital's minimum service standards, which were <20%. Nutrient adequacy on days 1 and 3 was lowest for protein and on day 2 for fat. Conclusion: The menu on days 1 and 3 did not meet the minimum hospital service standards of 22.9% and 29%, while the menu on day 2 met the minimum hospital service standards of <20%. Nutrient adequacy on days 1 and 3 was lowest for protein and on day 2 for fat. Keywords : Nutritional Adequacy, Food Waste